P12.04 The evidence for sexually transmitted infections as a marker for child sexual abuse: the physical signs of child sexual abuse 2nd edition 2015. (13th September 2015) - Rogstad, Karen; Thomas, Amanda; McIntosh, Neil; Christian, Cindy
Abstract : Introduction: In 2008 the RCPCH in collaboration with RCP (London) and Faculty of Forensic and Legal Medicine produced the only evidence based review on Physical Signs of Child Sexual Abuse (CSA). The evidence has been used in child protection cases including family and criminal proceedings in the UK and advised practitioners internationally. A further review of evidence with additional representation from American Academy of Paediatrics was undertaken to determine if changes to evidence statements are required. Methods: The 2008 search strategy identified all published primary research literature reporting STIs in relation to child sexual abuse or in children selected for non-abuse. For the 2015 publication, the search strategies were re-run on MEDLINE and EMBASE databases (Jan 2007–March 2014). Studies were selected according to certainty and quality of STI and CSA diagnosis. Results: Two additional studies were identified. One for HPV strengthened the evidence base for external genital warts (EGW) as a marker of CSA, reporting 50% of children sexually abused. The evidence base is "a significant proportion (31–58%) have been abused and a revised recommendation to refer children <13 yrs for child protection assessment. One study was for Neisseria gonorrheae also supported the previous evidence statement (sexual abuse reported in 36–83%). The evidence has not changed significantly; GC, CT, and TV are most likely sexually transmitted and for children with HPV a significant number are sexually transmitted. Referral to child protection services is advised for all under 13 yr olds with GC, CT, TV, EGW; and for syphilis, HIV/Hepatitis B/C/Herpes genitalis sexual abuse should always be considered if other modalities have been excluded; infection in the mother does not exclude CSA. Conclusion: Children under 13 yrs presenting with an STIs should have CSA considered and be referred for a child protection assessment unless (rarely) evidence to the contrary. Conflict of interest: KER has received sponsorship, speakers and consultancy fees from Pharma related to HIV therapy and HPV vaccines.